Early applications of ChatGPT in medical practice, education and research - Sedaghat, Sam (Clinical medicine, 2023)
ChatGPT, which can automatically generate written responses to queries using internet sources, soon went viral after its release at the end of 2022. The performance of ChatGPT on medical exams shows results near the passing threshold, making it comparable to third-year medical students. It can also write academic abstracts or reviews at an acceptable level. However, it is not clear how ChatGPT deals with harmful content, misinformation or plagiarism; therefore, authors using ChatGPT professionally for academic writing should be cautious. ChatGPT also has the potential to facilitate the interaction between healthcare providers and patients in various ways. However, sophisticated tasks such as understanding the human anatomy are still a limitation of ChatGPT. ChatGPT can simplify radiological reports, but the possibility of incorrect statements and missing medical information remain. Although ChatGPT has the potential to change medical practice, education and research, further improvements of this application are needed for regular use in medicine.
Online veröffentlicht am 26. Mai 2023, Artikelversion: 11. April 2024
Gesehen am 12.12.2023